If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2(6z + 8) = -9(z + 6) + 3 Reorder the terms: 7 + -2(8 + 6z) = -9(z + 6) + 3 7 + (8 * -2 + 6z * -2) = -9(z + 6) + 3 7 + (-16 + -12z) = -9(z + 6) + 3 Combine like terms: 7 + -16 = -9 -9 + -12z = -9(z + 6) + 3 Reorder the terms: -9 + -12z = -9(6 + z) + 3 -9 + -12z = (6 * -9 + z * -9) + 3 -9 + -12z = (-54 + -9z) + 3 Reorder the terms: -9 + -12z = -54 + 3 + -9z Combine like terms: -54 + 3 = -51 -9 + -12z = -51 + -9z Solving -9 + -12z = -51 + -9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '9z' to each side of the equation. -9 + -12z + 9z = -51 + -9z + 9z Combine like terms: -12z + 9z = -3z -9 + -3z = -51 + -9z + 9z Combine like terms: -9z + 9z = 0 -9 + -3z = -51 + 0 -9 + -3z = -51 Add '9' to each side of the equation. -9 + 9 + -3z = -51 + 9 Combine like terms: -9 + 9 = 0 0 + -3z = -51 + 9 -3z = -51 + 9 Combine like terms: -51 + 9 = -42 -3z = -42 Divide each side by '-3'. z = 14 Simplifying z = 14
| 1.6h-72=-4h-30 | | 30=x+3 | | 5y+2=4y+10 | | 3-4=2x+5 | | 3-6(-7y-4)=(-4y+8)-7 | | 3-4=2x-5 | | 4x+2-5y=7-6y | | .5n+5=3 | | 50.00+12.00s= | | c/3+c/6 | | 7(x+9)=7x-9 | | 80=9/5c+32 | | 3m+1=16 | | q=2p+8*p | | -1-2x=5x-71 | | x^2+-6= | | 6x^2+48=-12x | | -(-4-2r)=6.5-.5r | | 2975-500=440x | | 1/2q=9-2/5q | | 8-11x=3x+369 | | 8.39=x+.15x | | 5c+6=-9 | | 7(x+1)=7x-9 | | q=2p+8forp | | 2(1/3k-6)^2+(5/3k-6)+2=0 | | x^2-2x-3/4=0 | | 2/5m=1/3(2m-12) | | 4.9x^2+4x+3=0 | | 3=x+7-1 | | -5x-10=2-1x+4 | | 5a-3.5(-4-9a)=22+42.5a |